Protective role of intraperitoneally administered vitamin E and selenium in rats anesthetized with enflurane - Naziroglu, M (Springernature, 1999)
The aim of this investigation was to determine levels of liver vitamins A and E and blood biochemical and hematological parameters in the enflurane anesthesia of rats. Fifty adult male Wistar rats were used in this study All rats were randomly divided into five groups. The first and second groups were used as the control and anesthesia control groups, respectively, and only the placebo was intraperitoneally injected. The third group was intraperitoneally administered with vitamin E (dl-alpha-tocopheryl acetate, 100 mg/kg body weight), the fourth group with Se (Na2SeO3 1.5 mg/kg body weight), and the fifth group with vitamin E and Se (dl-alpha-tocopheryl acetate, 100 mg/kg body weight + Na2SeO3 1.5 mg/kg body weight). This administration was done for three times with overday intervals and the second, third, forth, and fifth group rats were taken to enflurane anesthetise for 2 h. The liver vitamin E level was slightly lower in the anesthesia control group than in control group. However, the liver vitamin E content was significantly (p < 0.05 and p < 0.01) increased in vitamin E, Se, and combination groups, whereas the vitamin A level in Liver was not statistically different. In general, plasma levels of alanine aminotransferase, creatin kinase, total bilirubin, urea, red blood cell counts, packet cell volume, and hemoglobulin values were significantly (p < 0.05 and p < 0.001) increased during the anesthesia and returned to near control values after the vitamin E plus selenium injection. However, administration of vitamin E had less effect on the hematological and biochemical parameters compared to that of selenium and their combination with vitamin E. However, the white blood cell count and levels of alkaline phosphatase, aspartate aminotransferase, total cholesterol, triglycerides, total protein, and creatinine were not statistically influenced by the anesthesia. In conclusion, we observed that plasma levels of some enzymes and metabolites were significantly increased in the enflurane anesthesia of rats, whereas the liver vitamin E levels were slightly decreased. Therefore, we observed that vitamin E and selenium have a protective effect against anesthesia complication, but the effect of selenium appears to be much greater than the vitamin E.
Keywords: anesthesia; vitamin E; selenium; enzymes; enflurane; rat